Sistem Distribusi Air Bersih Berbasis IoT dengan ESP8266 dan RTC untuk Optimalisasi Waktu Pengaliran - Rama Noveliandra; Rissa Nurfitriana Handayani (Universitas Merdeka Malang, 2025)
Efficient clean water distribution is essential to meet the needs of communities in various regions. This study aims to develop an Internet of Things (IoT)-based clean water distribution system using ESP8266 as the main controller for automatic and scheduled water flow timing. This system is able to regulate the opening and closing of taps on a schedule and allows manual control via mobile phone devices. The method used includes the integration of IoT technology with the Blynk application for real-time monitoring and control. The results of the study show that this system can optimize the use of water resources, reduce waste, and ensure a more regular distribution of clean water. In addition, the flexibility of control via mobile phones makes it easy for users to manage water distribution. This study offers an innovative solution that can be applied to improve the efficiency of clean water distribution in various regions